Pengakuan dan pengukuran pendapatan berdasarkan PSAK No. 23 - Tri Wulandari; Nur Aliffah Adi Saputri; Rizka Febriana Nur Laili; Septi Nur Fitriani; Ardyan Firdausi Mustoffa (Jurnal Bina Akuntansi, 2023)
The company is an organization consisting of several elemental groups that are quantitative in nature and have achievement targets that serve as a measure of the success of the company's performance. Several types of companies aim to gain profits, one of which is a manufacturing company or an industrial company whose main activity is to produce or process raw materials become raw materials and sell them to consumers. Revenue is the amount of money that a company can receive from its activities and most of it comes from selling products or services to consumers. Revenue recognition can be recognized if it meets the criteria. This research is a type of descriptive research. explore this research using secondary data with the population used, namely all research results and articles related to recognition and measurement revenue based on PSAKi noi 23. The sample in this research is research that uses data for 2018-2022. The results of the literature review show that revenue recognition has two types of recording, namely accrual basis and cash basis where not all companies meet PSAKi criteria in recording. In addition, the measurement of profit must be measured by the fair value that the company will receive and the compensation that the company will receive.